2020
DOI: 10.32718/ujvas3-2.07
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of individual indicators of protein metabolism in the body of broiler chickens on the background of combined stress when included in the diet “Reasil Humic Vet” + “Laktin” and “Reasil Humic Health”

Abstract: The body of  broiler chickens is characterized by a high metabolism, which promotes rapid growth and development, but their performance indicators are largely related to housing conditions, which are known to include a number of technological stressors. With the development of stress in the body of poultry changes the course of metabolic processes, which causes changes in all types of metabolism, including protein. The aim of the study was to determine the changes in individual indicators of protein me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…An increase in the number of bifidobacteria, which is the basis of the perineal and cavity microflora, led to an increase in the vitality of vitamin products B6 and B 12 in process of vitality, which had a positive effect on the intensity of oxidative-reducing processes in the system of erythron and hemopoiesis of piglets in the S group. Adaptation of the system of protein metabolism in animals of this group was shown by an increase in the synthetic function of hepatocytes, transport and immune function of the blood, due to the basic properties of amber acid, as the main component of the "Biovir" (Stoyanovskyy et al, 2020). It is a universal biogenic metabolism stimulator in cells, that is, the natural endogenous substrate of oxidation-reduction processes (Krebs cycle) without additional energy expenditure, which leads to the activation of biosynthesis of proteins at different levels (Roman et al, 2020).…”
Section: Tablementioning
confidence: 97%
See 1 more Smart Citation
“…An increase in the number of bifidobacteria, which is the basis of the perineal and cavity microflora, led to an increase in the vitality of vitamin products B6 and B 12 in process of vitality, which had a positive effect on the intensity of oxidative-reducing processes in the system of erythron and hemopoiesis of piglets in the S group. Adaptation of the system of protein metabolism in animals of this group was shown by an increase in the synthetic function of hepatocytes, transport and immune function of the blood, due to the basic properties of amber acid, as the main component of the "Biovir" (Stoyanovskyy et al, 2020). It is a universal biogenic metabolism stimulator in cells, that is, the natural endogenous substrate of oxidation-reduction processes (Krebs cycle) without additional energy expenditure, which leads to the activation of biosynthesis of proteins at different levels (Roman et al, 2020).…”
Section: Tablementioning
confidence: 97%
“…The use of the additive was positive for leveling changes in the protein metabolism system due to the development of an adaptive syndrome, which was manifested by an increase in the content of total protein by 9.4%, βglobulins -by 18.3 % (P < 0.05), γ-globulins -by 27,2-26.8 % (P < 0.05) compared with control. Our previous studies (Stoyanovskyy et al, 2020) showed that peptides of cell walls of lactobacillus and bifidobacteria supplements of "Biovir" had immunostimulatory properties for lymphoid tissue of the intestinal mucosa of piglets and served as substrate for the growth and development of its microbiocenosis. An increase in the number of bifidobacteria, which is the basis of the perineal and cavity microflora, led to an increase in the vitality of vitamin products B6 and B 12 in process of vitality, which had a positive effect on the intensity of oxidative-reducing processes in the system of erythron and hemopoiesis of piglets in the S group.…”
Section: Tablementioning
confidence: 99%
“…Виникнення метаболічних хвороб пов'язано з якістю та режимом годівлі птиці на великих промислових комплексах (Yousefi et al, 2005;Vodolazhchenko, 2011;Verner, 2013;Novozhylova, 2014). Використання для годівлі птиці різноманітних сорбентів, пре-та пробіотиків, біогенних стимуляторів росту, біологічно активних речовин стало невід'ємною складовою рецептур комбікормів (Leeson, 1999;Mashkin, 2010;Stoyanovskyy et al, 2020;Yaremchuk et al, 2020). Проте навіть такі заходи не убезпечують птицю від метаболічних хвороб.…”
Section: вступunclassified
“…It became known that probiotics can modulate the redox status of the recipient due to their ability to chelate metal ions, and antioxidant systems, thus regulating signaling pathways and enzymes that produce reactive forms of oxygen and intestinal microbiota. 10,11 There is scientific interest in finding potential probiotic strains that may exhibit powerful antioxidant properties along with health benefits. In vitro and in vivo research have ascertained that probiotics exhibit antioxidant potential.…”
Section: Introductionmentioning
confidence: 99%